EFFORTS TO INCREASE STUDENT INTEREST IN ENTREPRENEURSHIP DURING THE COVID-19 PANDEMIC - Debora Tambunan; Asriyana Asriyana; Iventura Fitra Uli Tamba; Elisabeth Nainggolan; Inda Arfa Syera (Jurnal Mantik, 2022)
The purpose of this study is to analyze the effect of entrepreneurial education, family environment, and income expectations on interest in entrepreneurship at the Multi Smart Business Management College. The population and sample in the study were 54 students who had completed entrepreneurship courses. Data collection using questionnaires and data analysis using multiple linear regression analysis. The results of partial and simultaneous data analysis of entrepreneurship education, family environment, and income expectations have a significant effect on students' interest in entrepreneurship. The most dominant variable or which is considered to have a major influence in increasing a student's interest in entrepreneurship is entrepreneurship education